Factors predicting complications following open reduction and internal fixation of intra-articular distal radius fracture - Kong, Lingde; Li, Hua; Zhou, Yanqing; Zhang, Bing; Han, Quan; Fu, Meng (Frontiers in Surgery, 2024)
Objective To determine the incidence and predictors of complications after open reduction and internal fixation (ORIF) of intra-articular distal radius fracture (IADRF) with a minimum follow-up of 12 months.Methods Medical records and outpatient follow-up records were retrospectively reviewed to collect medical, surgical and complication data on consecutive patients who had undergone an ORIF procedure for an IADRF between January 2019 and June 2022. Data included demographics, comorbidities, injury, surgical characteristics, and laboratory findings on admission. The multivariate logistic regression model was constructed to identify significant predictors, with composite of any complications occurring within 12 months after the operation as outcome variable, and potentially a range of clinical data as independent variables. The magnitude of the relationship was indicated by the odds ratio (OR) and the 95% confidence interval (CI).During the study period, 474 patients were included and 64 had documented complications (n=73), representing an accumulated rate of 13.5%. Among them, carpal tunnel syndrome was the most common, followed by tenosynovitis caused by tendon irritation/rupture, superficial or deep wound infection, complex regional pain syndrome (CRPS) type 1, radial shortening (≥4mm), plate/screw problems and others. The multivariate results showed experience of DRF surgery < 30 cases (OR 2.2, 95% CI 1.6 to 3.5), AO type C fracture (OR 1.7, 95% CI 1.2 to 2.9), initial lunate facet collapse ≥5mm (OR 4.2, 95% CI 1.4 to 8.9) and use of temporary external fixation before index surgery (OR 2.4, 95% CI 1.5 to 4.3) were significantly associated with increased risk of complicationsThese findings may aid in patient counseling and quality improvement initiatives, and IADRF should be directed by an experienced surgeon.